2016
DOI: 10.1364/oe.24.011023
|View full text |Cite
|
Sign up to set email alerts
|

Broadband circularly polarizing dichroism with high efficient plasmonic helical surface

Abstract: We propose and experimentally demonstrate a broadband and high efficient circularly polarizing dichroism using a simple single-cycle and single-helical plasmonic surface array arranged in square lattice. Two types of helical surface structures (partially or completely covered with a gold film) are investigated. It is shown that the circular polarization dichroism in the mid-IR range (3µm - 5µm) can reach 80% (when the surface is partially covered with gold) or 65% (when the surface is completely covered with g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 21 publications
2
26
0
Order By: Relevance
“…On drawing the helices close together, their mutual action becomes more pronounced, and the resonance starts exhibiting a blue shift (BS) (Figure c). A similar blue shift of the resonance due to the mutual influence of planar and helical metal metasurface elements was previously observed . The blue shift of the fundamental resonance observed on decreasing the distance between helices is beneficial for the fabrication of structures to control shorter‐wavelength radiation.…”
Section: Characterization and Discussionsupporting
confidence: 77%
“…On drawing the helices close together, their mutual action becomes more pronounced, and the resonance starts exhibiting a blue shift (BS) (Figure c). A similar blue shift of the resonance due to the mutual influence of planar and helical metal metasurface elements was previously observed . The blue shift of the fundamental resonance observed on decreasing the distance between helices is beneficial for the fabrication of structures to control shorter‐wavelength radiation.…”
Section: Characterization and Discussionsupporting
confidence: 77%
“…The experimentally retrieved CD reaches a maximum value of approximately 2.5 %. It should be emphasized again that this value is recorded for a single nanohelix, in contrast to most of the studies reporting on CD values for large arrays of chiral nanostructures [13,40,43,[46][47][48]51]. In the case discussed here, a single nanohelix with an approximate diameter of only 120 nm is excited by a Gaussian beam focused weakly down to a spot with diameter of around 1.2 µm (full width at half maximum at λ = 1450 nm).…”
Section: Chiroptical Response Of a Single-loop Nanohelixmentioning
confidence: 67%
“…It is observed that the spectral CPD (defined as CPD = T RCP − T LCP , where T RCP and T LCP are the transmission coefficients of the RCP and LCP incidences, respectively) in the entire 3–5 µm region is flat and greater than 0.7. It should be mentioned that this high and flat CPD in the wide spectral region is achieved with a gradient phase distributed structure (i.e., with varied helical units over entire device), which is in contrast to the previous reports using uniform structures …”
Section: Theory and Structure Designmentioning
confidence: 63%
“…Dichroism metasurfaces that exhibit strong optical activity (OA) and circular polarization dichroism (CPD) due to the flexible design of metamolecules in terms of structure, dimension, and materials, have attracted much attention recently. 3D chiral metamaterials exhibit superb CPD in the middle‐infrared band that transmits the opposite handedness of the circular polarization and structural helix such as the 3D gold helix wires array and 3D gold helical surface array due to the plasmonic effect and the chirality matching/mismatching between the metamaterial and the incidence. In an alternative approach to the use of the 3D chiral metamaterials, strong CPD can also be achieved using a planar chiral metasurface with broken in‐plane mirror symmetry, with examples such as an etched Z‐shaped Si metasurface and L‐shaped gold metasurface at telecom wavelengths and giant intrinsic chiro‐optical activity with TiO 2 gammadions overlaid on a TiO 2 thin film on a glass substrate at 540 nm …”
Section: Introductionmentioning
confidence: 99%